Automorphisms of Surface Groups of Genus Two - Abu Osman, M.T (1988)
The mapping class group ofa surface is a quotient of the automorphism group Aut+rof the surface group by its normal subgroup of inner automorphism. The determination ofAut+r may be looked upon as an extension problem. This paper will give a presentation ofAut+r where r is a surface group ofgenus two. The extension to Seifert fibre group will be given.